“Sô particularmente profissional, tenho experiência”: trabalhadores e redes de convivência desde tenra idade no oeste paranaense (1960-2021) - Morais , Patricia Vieira (2022)
This master’s thesis discusses the experiences those who have been working from when they were very young and the relationships with those living together, starting in the 1960s to the present, in Western Paraná. I understand this research problem based on the process by which these people make themselves workers in the midst of certain ways of living, pressures and expectations. I try to understand the way in which the insertion in the work activities integrates these ways of life, at the same time as they deal with several other confrontations that emerge from their social condition and the affective bonds built. Besides, I examine the historicity of these practices, in dialogue with the meanings produced by workers who have this experience, debating legislation, socially constructed values, and connections with governmental agencies. I approach all this through documentation that indicates evidence of these relations, for example: interviews made with people who have worked ever since childhood, residents of Western Paraná; interviews with employees of government institutions in the region; police inquiries from the Civil Court referring to the County of Toledo, located in the collection of the Documentation, Information and Research Center; statistical indexes, especially the one prepared by the Brazilian Institute of Geography and Statistics (IBGE, 2010), linked to the Child Labor Eradication Program; documents of social assistance agencies of cities in Western Paraná. These sources show the research subjects in different spaces and relationships, and these networks of conviviality as controversial, where identifications and differences are created.